Creative Economy Potential in Developing Local Coffee-Based Products in Lahat Regency - Sudin Sudin; I Gusti Nyoman Surya Utama; Nurul Karima; Reza Amelia (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Coffee is a leading commodity with a strategic role in the regional economy, including in Lahat Regency, South Sumatra Province. Although this region has great potential as a producer of high-quality coffee, the main challenge faced is the low level of product innovation, which results in weak competitiveness in both national and international markets. The population in this study consists of all coffee MSMEs, totaling 100 business units, based on data from the Office of Cooperatives and MSMEs in 2025. The sampling technique used is a saturated sample, in which the entire population serves as the research sample. Data was collected through an online questionnaire addressed to the owners or managers of coffee MSMEs. Data analysis was conducted using Smart PLS. This study analyzes the effect of innovation, product quality, and product availability on consumer satisfaction of coffee MSMEs in Lahat, with government support as a moderating variable. The results show that product availability and government support have a significant effect on satisfaction, whereas product quality does not.